2018
DOI: 10.1097/paf.0000000000000382
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Road Traffic Vehicle Collisions With Pedestrian Victims

Abstract: Fatal car-to-pedestrian collisions regularly appear in the forensic pathologist's routine, particularly in places of extended urbanization. Postmortem computed tomography has gained an exceptional role to supplement autopsy worldwide, giving information that is supplementary or complimentary to conventional autopsy. In this retrospective study, a total number of 320 findings in a series of 21 pedestrians fatally hit by cars and trucks of both postmortem computed tomography and autopsy were correlated. Accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Overall, head, face, and neck injuries were the most common (71.4%, n ¼ 40) followed by thorax (64.3%, n ¼ 36), and head trauma was the most common cause of death. Of the 56 articles, only 10 articles in the present review indicated that radiological findings supplemented autopsy observations (22,35,37,39,53,57,58,61,62,70). Teresinski et al mentioned the use of radiology to diagnose injuries for accident reconstruction in two articles but whether imaging supplemented their studies was unclear (27,40).…”
Section: Sample Size and Originmentioning
confidence: 76%
See 3 more Smart Citations
“…Overall, head, face, and neck injuries were the most common (71.4%, n ¼ 40) followed by thorax (64.3%, n ¼ 36), and head trauma was the most common cause of death. Of the 56 articles, only 10 articles in the present review indicated that radiological findings supplemented autopsy observations (22,35,37,39,53,57,58,61,62,70). Teresinski et al mentioned the use of radiology to diagnose injuries for accident reconstruction in two articles but whether imaging supplemented their studies was unclear (27,40).…”
Section: Sample Size and Originmentioning
confidence: 76%
“…Similarly, another article published in the same year used data from 254 cases from 2006 (48). Two articles that were published in 2018 did include recent cases but had smaller sample sizes of 21 and 33 cases, and the authors focused on radiologic imaging and cardiac injuries, respectively (56,57).…”
Section: Study Periodmentioning
confidence: 99%
See 2 more Smart Citations
“…The best results for reconstructive purposes are achieved by combining autopsy and postmortem imaging, as shown below. However, this combined method may not be possible because of limited economic resources (3,10,11).…”
Section: Discussionmentioning
confidence: 99%